Law Enforcement and Victim Protection in Online Gender-Based Violence: A Case Study of The Distribution of Public Figures’ Private Content in Indonesia - Shafira Dita Sasmita; Chisa Belinda Harahap (Deviance Jurnal Kriminologi, 2026)
This study examines law enforcement and victim protection in cases of online gender-based violence, particularly the non-consensual distribution of public figures’ private content in Indonesia. Using a qualitative case study approach, the research analyzes how digital space transformation has intensified new forms of social harm, including violations of privacy, dignity, and human rights. The findings reveal that victims experience multidimensional impacts such as psychological distress, social stigma, and marginalization, while perpetrators exploit anonymity and rapid information dissemination to evade accountability. Although Indonesia has established legal frameworks to address cybercrime, gaps remain in implementation, victim protection mechanisms, and institutional responsiveness. From a sociological perspective, law is not only a normative system but also a social instrument that must adapt to digital dynamics. This study highlights the need for more adaptive legal enforcement, integrated institutional coordination, and victim-centered protection policies to ensure justice and strengthen public trust in the legal system within the digital era.